Influence of maternal age on intracytoplasmic sperm injection outcome and global deoxyribonucleic acid methylation in women undergoing intracytoplasmic sperm injection cycle - Laqqan, Mohammed M.; Yassin, Maged M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Intracytoplasmic sperm injection needs sufficient oocytes of high quality in order to increase the rate of fertilization and pregnancy. This study was designed to investigate the influence of maternal age on the ICSI outcomes in women undergoing to first ICSI cycle and to evaluate the influence of maternal age on global DNA methylation. Methods: A total of 242 females were included in this study with a mean age of 30.5±7.3 years. The participants were divided into three groups depending on women’s age≤25, N=70; 26-35, N=102 and>35, N=70). The genomic DNA was isolated from the blood samples, then the global DNA methylation was evaluated using ELISA. Results: A significant reduction has been found in the level of anti-Müllerian hormone (AMH), total number of the collected oocyte, mature oocytes, fertilized oocytes and number of embryos transferred in the older females compared to the younger group (p<0.001). While a significant increase has been found in global DNA methylation level in the older females compared to the younger group (p<0.001). A positive significant correlation has been found between global DNA methylation level and maternal age (p<0.001). In contrast, a negative significant correlation has been shown between AMH level, mature oocytes and maternal age (p<0.001). Conclusions: Maternal age has a significant influence on the number of mature oocytes, number of embryos transferred and global DNA methylation. The pregnancy chance is more in the age group less than 35 years.